POLA MAKAN, KECUKUPAN GIZI DAN STATUS GIZI BALITA PADA KELUARGA MISKIN DI PERUMNAS MANDALA, KELURAHAN KENANGAN BARU - Chintya Nurul Aidina; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Food patterns of under five years old in poor families consume staple food such as rice, side dishes, vegetables and fruits are very limited. This study aimed to determine food patterns, nutrition adequacy and nutritional status of children in poor families. The research was a descriptive survey, cross-sectional design. Sample in this study consisted of 65 children taken from 196 children. Respondents in this study were mothers of children under five. Collecting data on family characteristics obtained through interviews using a questionnaire, toddler food consumption data obtained through food recall and food frequency data using scales weight toddlers underfoot and data using microtoise toddler height. The results showed that the diet of children under five according to the type of food consumed staple is rice, side dishes are consumed eggs, and tempeh, vegetables are often consumed are spinach, and fruits consumed is papaya. Generally good level of energy consumption by 53,8%, good protein consumption level of 100%, and the rate of consumption of good fats 46,2%. Nutritional status (BB/U) are good at 92,3%, nutritional status (TB/U) are normal at 66,2% and nutritional status (BB/TB) are normal at 92,3%. Suggestions of this study was to local health officials are expected to focus more on education, especially for mothers of children under five in improving nutrition in particular on the provision of food within the household level which is very important to support improved nutrition of children under five. Keywords: food pattern, nutrition adequacy, nutritional status, children under five years old, poor families